Brody Cox: capstone - Cox, Brody, artist (Colorado State University. Libraries, 2020)
The artist's statement: My approach to metal centers around form and color. Whenever I start a piece, I push the final version to be visually transformed from how it started. How can rigid metal be seen as natural and organic? What if the color of copper became jet black? These are the types of questions I ask myself when making work, and the ones that push my material to take new shapes and depictions. When designing a project, I am always drawn towards ambiguity and abstraction. My favorite pieces leave the viewer uncertain, but wanting to know more. The mysterious and weird nature of my work tries not to be objective, so it can be read differently from person to person. It is a challenge to make something visually abstract, but also carry intentionality. I am constantly trying to find this balance as I work, but I am the most satisfied when I do.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metals